PENYEBAB DITOLAKNYA SUATU KLAIM ASURANSI (STUDI PENELITIAN PT PRUDENTIAL LIFE ASSURANCE MEDAN) - Zulkifli, Suhaila; Panjaitan, Melati; Arrahman, Gia; Silitonga, Jhosua (Hukum Universitas Sari Mutiara Indonesia, 2020)
Insurance is coverage or an agreement between two parties called the insured and the insurer. Where the insured is obliged to pay contributions / premiums in accordance with the products purchased to the insurer and while the insurer has the obligation to fully guarantee the contribution / premium contribution payer in the event that something happens to the first party or his belongings in accordance with the agreement that has been made. Data collection methods in this study were interviews and literature studies. An important issue that can be concluded from this research is the implementation of the Prudential Carli Br Ginting insurance agreement at the Medan City Branch of Prudential Life Assurance with the insured which has not been fully implemented due to several inhibiting factors that led to the rejection of the insured's claim. This research focuses on what causes a claim to be hampered along with the settlement made by PT Prudential Life Assurance Medan City as a form of responsibility to the insured